Insulin Resistance and High Blood Pressure: Mechanistic Insight on the Role of the Kidney - Gabriele Brosolo; Andrea Da Porto; Luca Bulfone; Antonio Vacca; Nicole Bertin; Laura Scandolin; Cristiana Catena; Leonardo A. Sechi (Biomedicines, 2022)
The metabolic effects of insulin predominate in skeletal muscle, fat, and liver where the hormone binds to its receptor, thereby priming a series of cell-specific and biochemically diverse intracellular mechanisms. In the presence of a good secretory reserve in the pancreatic islets, a decrease in insulin sensitivity in the metabolic target tissues leads to compensatory hyperinsulinemia. A large body of evidence obtained in clinical and experimental studies indicates that insulin resistance and the related hyperinsulinemia are causally involved in some forms of arterial hypertension. Much of this involvement can be ascribed to the impact of insulin on renal sodium transport, although additional mechanisms might be involved. Solid evidence indicates that insulin causes sodium and water retention, and both endogenous and exogenous hyperinsulinemia have been correlated to increased blood pressure. Although important information was gathered on the cellular mechanisms that are triggered by insulin in metabolic tissues and on their abnormalities, knowledge of the insulin-related mechanisms possibly involved in blood pressure regulation is limited. In this review, we summarize the current understanding of the cellular mechanisms that are involved in the pro-hypertensive actions of insulin, focusing on the contribution of insulin to the renal regulation of sodium balance and body fluids.